2017
DOI: 10.1302/2046-3758.66.bjr-2017-0023
|View full text |Cite
|
Sign up to set email alerts
|

Stem cell therapy for enhancement of bone consolidation in distraction osteogenesis

Abstract: ObjectivesDistraction osteogenesis (DO) mobilises bone regenerative potential and avoids the complications of other treatments such as bone graft. The major disadvantage of DO is the length of time required for bone consolidation. Mesenchymal stem cells (MSCs) have been used to promote bone formation with some good results.MethodsWe hereby review the published literature on the use of MSCs in promoting bone consolidation during DO.ResultsStudies differed in animal type (mice, rabbit, dog, sheep), bone type (fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 51 publications
(65 reference statements)
0
20
0
Order By: Relevance
“…Therefore, the scientists are constantly exploring new medical tools [14,20,21,22,23]. The emergence of stem cell therapy brings new hope for the treatment of these diseases [24,25]. The homing and low immunogenicity of MSC make them ideal seed cells for stem cell therapy [26].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the scientists are constantly exploring new medical tools [14,20,21,22,23]. The emergence of stem cell therapy brings new hope for the treatment of these diseases [24,25]. The homing and low immunogenicity of MSC make them ideal seed cells for stem cell therapy [26].…”
Section: Introductionmentioning
confidence: 99%
“…The long treatment duration of DO leads to frequent complications; therefore, shortening the treatment period may provide significant clinical benefits. Transplantation of MSCs could accelerate new bone formation, which represents a potential strategy for shortening DO treatment time [14]. Although autologous MSC transplantation has advantages with regard to safety and efficiency in tissue regeneration, the procedure has several inevitable disadvantages, including source limits, risk of donor site infection and age-related impairment of MSC function [21].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that MSCs are effective in promoting bone healing and enhancing bone consolidation in DO animal models [1,7,10À13]. The authors' recent review article addressed the successful applications of MSCs in DO systematically in various animal species (mice, rabbits, dogs, sheep), bone sites (femur, tibia, skull), DO protocols and cell transplantation methods [14]. Systemic reviews from other groups have also addressed the efficacy of locally applied MSCs in promoting bone formation in mandible DO animal models [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Managing massive bone loss following traumatic open fracture is challenging as normal healing is compromised by poor vascularity. Recent studies support the use of stem cells for musculoskeletal applications and improving the reparative process 1 - 3 .…”
Section: Introductionmentioning
confidence: 95%